Influence of stratification, heat and removal of teguments on breaking of seed dormancy in almond - García-Gusano M.; Martínez-Gómez P.; Dicenta F. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
The effect of stratification, heat, and endocarp and tegument removal on the breaking of seed dormancy was studied in 3 almond cultivars. In the first assay, the nuts with endocarp were stratified at 7 degrees C for 15 weeks. In the second, the nuts with endocarp were stratified at 7 degrees C for 4 weeks. Then, non-germinated seeds were kept at 22 degrees C for 7 weeks more to promote germination. Then, the remaining non-germinated nuts were cracked and the tegument was removed. The percentage of germinated seeds of each cultivar was recorded weekly in both assays. The results showed a different effect of each treatment on seed germination for each cultivar, related to their flowering time. The removal of the endocarp and the tegument in seeds that had not fulfilled their chilling requirements, produced the same effect as stratification and, finally, similar percentages of seed germination were observed in comparison with the first treatment.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)